Alpha-1 Antitrypsin Deficiency Presenting with MPO-ANCA Associated Vasculitis and Aortic Dissection - Bram M. Voorzaat; Jan van Schaik; Stijn L. P. Crobach; Catharina S. P. van Rijswijk; Joris I. Rotmans (Case Reports in Medicine)
The combination of alpha-1 antitrypsin (AAT) deficiency, ANCA-vasculitis, and aortic aneurysm has been rarely described in literature. We report an eventually fatal case in a 70-year-old patient who initially presented with giant cell arteritis and ANCA associated glomerulonephritis. Several years later, he presented with aortic dissection due to large vessel vasculitis, raising the suspicion of AAT deficiency, as two first-line relatives had chronic obstructive pulmonary disease, while they never smoked. This diagnosis was confirmed by AAT electrophoresis and immunohistochemistry on a temporal artery biopsy. Considering AAT deficiency in these cases might lead to a more timely diagnosis.